2021
DOI: 10.3390/molecules26030772
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of MeON-Glycoside Derivatives of Oleanolic Acid by Neoglycosylation and Evaluation of Their Cytotoxicity against Selected Cancer Cell Lines

Abstract: A series of C-3 and C-28 MeON-neoglycosides of oleanolic acid were designed and synthesized by neoglycosylation as potential antiproliferative agents. Their cytotoxicity was evaluated in vitro against five human cancer cell lines: human non-small cell lung cancer cell line (A549), human melanoma cell line (A375), human colon cancer cell line (HCT116), human liver carcinoma cell line (HepG2), human breast adenocarcinoma cell line (MCF-7) by the Cell Counting Kit-8 (CCK-8) assay. Most of C-3 and C-28 MeON-neogly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Oleanolic acid (OA), a natural triterpenoid compound, has antitumor activity in a variety of tumors [ 116 , 117 , 118 ]. A study found that OA could inhibit NOTCH signaling, resulting in promoting mitochondrial apoptosis and inhibiting proliferation in a dose-dependent manner in osteosarcoma [ 57 ].…”
Section: Osteosarcoma Treatment Strategy Based On Notch Signalingmentioning
confidence: 99%
“…Oleanolic acid (OA), a natural triterpenoid compound, has antitumor activity in a variety of tumors [ 116 , 117 , 118 ]. A study found that OA could inhibit NOTCH signaling, resulting in promoting mitochondrial apoptosis and inhibiting proliferation in a dose-dependent manner in osteosarcoma [ 57 ].…”
Section: Osteosarcoma Treatment Strategy Based On Notch Signalingmentioning
confidence: 99%
“…Du et al [118] synthesized new MeON-Glycoside derivatives of OA by neog lation (general structure: compound 29, Table 7). Due to the large number of deriv we chose those with the strongest cytotoxic activity (IC50 < 10 µM), in which modifi were introduced at the C3 carbon: In another study, A375 cells were treated with rhodamine B-conjugated OA In recent years, many studies have focused on its antitumour effect and cyto towards a wide array of cancer cell lines, including melanoma.…”
Section: Betulin and Betulinic Acidmentioning
confidence: 99%
“…Du et al [118] synthesized new MeON-Glycoside derivatives of OA by neog lation (general structure: compound 29, Table 7). Due to the large number of deriv we chose those with the strongest cytotoxic activity (IC50 < 10 µM), in which modifi were introduced at the C3 carbon: In recent years, many studies have focused on its antitumour effect and cyto towards a wide array of cancer cell lines, including melanoma.…”
Section: Betulin and Betulinic Acidmentioning
confidence: 99%
See 2 more Smart Citations